Automatic NC Toolpath Generation for 3D Sculptured Features Extracted from 2D Image - Thakur, Rahul (My University, 2014)
In the present work an attempt has been made for web based automation of Look Alike 3-Dimensional image design features using online application programming interface (API) environment. A web based environment has been developed for providing interactive access to automatic image toolpath generation. In the present work, the domain of 3D design features is restricted to image feature designing. The concept demonstrated in the present dissertation work can be extended for web-based automation of all types of 3D solid/surface modelling which is permitted inside any commercial CAD package supporting API based macro development. The webbased interactive API macros will help the client to choose various parameters required for look alike 3D design creation and help them incorporate their creativity to create the design they like. The design model is made available on the webpage so that the user can get a feel of what is being designed by him. When the design get finalized, the CAD model is saved in the required format at the server end. In the present work, the CAD model is saved in point cloud data format which can be further used as an input for downstream applications like rapid prototyping, NC toolpath generation or automatic assembly operations etc. The point cloud data directly is then further used for the generation of toolpath by using two methods Raster toolpath and Contour Toolpath. This toolpath file can be used with any customized machine available with customer to manufacture the feature. The overall design strategies for creating some 3D design within some pre-defined families can be made more productive, cost effective and remotely excessive. A lot of research has been going in the field of 3D design automation and modelling which also uses Web Based application for real time data exchange and approvals. Under the present work, an initiative has been taken for development of web-enabled client based designing and toolpath generation for image sculpture on the aluminum sheet by the processed algorithms. This is the ultimate aim of the present work is to develop an integrated design and manufacturing environment which can be used by anyone even a engineering background or a non-engineering background person or a hobbyist.
ME-CAD/CAM-Dissertation
Keywords: NC toolpath from 2D image; CNC machining; 3D Sculptured surface; mechanical engineering; MED